Commentary on the judgement of the Supreme Court, file No. V CSK 709/15 - Lisowska, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
This article was a commentary on the judgments of the Regional Court and Court of Appeal, issued in the case of marriage annulment brought by M. Z. against J. Z., where the defendant had suffered from paranoid schizophrenia and hid this fact from her future husband. The publication contained arguments questioning the validity of the decision issued by Court of First Instance. In addition, the article set forth premises approving of the ruling of Court of Second Instance.